Accurate process-hotspot detection using critical design rule extraction - Yu, Yen-Ting; Chan, Ya-Chung; Sinha, Subarna; Jiang, Iris Hui-Ru; Chiang, Charles (Proceedings of the 49th Annual Design Automation Conference, 2012)
In advanced fabrication technology, the sub-wavelength lithography gap causes unwanted layout distortions. Even if a layout passes design rule checking (DRC), it still might contain process hotspots, which are sensitive to the lithographic process. Hence, process-hotspot detection has become a crucial issue. In this paper, we propose an accurate process-hotspot detection framework. Unlike existing DRC-based works, we extract only critical design rules to express the topological features of hotspot patterns. We adopt a two-stage filtering process to locate all hotspots accurately and efficiently. Compared with state-of-the-art DRC-based works, our results show that our approach can reach 100% success rate with significant speedups.